Pengaruh Pelatihan, Kompetensi, dan Motivasi Kerja terhadap Kinerja Karyawan Group CTO Office PT Indosat - Rahma Sari Dewi; Eny Ariyanto (Telaah Bisnis, 2017)
Abstract This study aims to determine and analyze the effect of training, competence and work motivation on employee performance at CTO Office Group PT Indosat Tbk Jakarta. The research population is all employees of CTO Office Group PT Indosat Tbk Jakarta, which is 100 people. Sampling methode using the census technique, that is because the population size is relatively small then all members of the population is taken into the sample research. Primary data were collected using questionnaires and secondary data were obtained from various sources such as journals, archived documents and literature. Hypothesis testing of research using multiple linear regression statistic technique. The results of hypothesis testing proved that the variables of training, competence and motivation of each work partially have a significant positive effect on employee performance. Coefficient R2 = 0.727, which shows the findings that the variables training, competence and work motivation simultaneously able to explain significant variations of changes in employee performance variables of 72.7%.